Fachbezogene Core Practices in der Lehrkräftebildung am Beispiel des Pädagogikunterrichts - Wüllner, Sabrina; Schellenbach-Zell, Judith; Rochnia, Michael

Bildungsplan Stadtteilschule. Jahrgangsstufen 5-11. Pädagogik - Dube, Alexandra; Jäger, Christina; Knöpfel, Eckehardt; Wüllner, Sabrina

Bildungsplan Gymnasium. Sekundarstufe I. Pädagogik - Dube, Alexandra; Jäger, Christina; Knöpfel, Eckehardt; Wüllner, Sabrina

Direct assessment of the influence of pose repeatability on the accuracy of dimensional measurements for computed tomography systems with high degrees of freedom - Butzhammer, Lorenz; Handke, Niklas; Wittl, Simon; Herl, Gabriel; Hausotte, Tino (Measurement Science and Technology)
Abstract Industrial x-ray computed tomography (CT) systems with high geometric flexibility are increasingly utilized for large-scale measurement objects or challenging measurement tasks. To maintain high accuracy when deviating from the established circular scan trajectory, trajectory calibration methods using multi-sphere reference objects with known marker positions are commonly employed. These multi-sphere objects can either be scanned together with the measurement object (online trajectory calibration) or in a separate scan (offline trajectory calibration). While offline calibration increases machine time, it generally results in higher scan quality. However, a sufficient pose repeatability is necessary to ensure comparable or even superior accuracy to online calibration. In this contribution, we present a straightforward procedure to compare both types of trajectory calibration in a way that the differences of the results can directly be traced back to the influence of the pose repeatability. The multi-sphere reference object is not only used for trajectory calibration, but simultaneously as a measurement object for repeated measurements. The methodology is tested on both a twin robotic CT system and a conventional CT system that is additionally equipped with a hexapod manipulator for adaptive object tilting. Results showed, independent from the type of trajectory calibration, systematic measurement errors in the order of 10 −5 –10 −4 of measured sphere distances and sphericity values below 50 μ m . For sphere distances, random errors were increased by a factor of 5 due to the offline trajectory calibration, but were still low ( < 1 μ m ) in comparison to systematic errors and the spread of different measurement features. Overall, both investigated systems demonstrated sufficient positioning repeatability for offline trajectory calibration. The method is in general also applicable to any other types of manipulator systems used for CT devices. It provides a workflow for the decision which type of trajectory calibration is preferable for a given CT system.

Practical Approaches for Determining the Structural Resolution Capability of X-ray Computed Tomography Measurement Tasks - Busch, Matthias; Hausotte, Tino (Metrology)
The structural resolution describes the ability of a measuring device to detect small structures on the surface of a component or test specimen by means of a quantitative value. However, the structural resolution in the computer tomograph depends on the object and must therefore be determined separately for each measurement task. The previous approaches to structural resolution determination are only related to test specimens. In this paper, less discrete approaches based on a circular pattern are presented, which can be integrated into the measured component. A voxel-based methodology as well as two surface-based methodologies are described. The investigation results regarding the effect of the component position on the structural resolution are obtained on the basis of real CT measurements. A comparison is also completed with the well-known hourglass method. The results show that the resolution depends on the object being measured, with similar values being obtained for the same object using different methods.

Task-specific scan trajectory modification for dimensional X-ray computed Tomography with high throughput - Butzhammer, Lorenz; Hausotte, Tino (tm - Technisches Messen)
Zusammenfassung Eine Erweiterung der Scantrajektorie für die industrielle Röntgen-Computertomographie von einer kreisförmigen Form (entsprechend einer 360°-Rotation des Messobjekts) hin zu frei wählbaren Aufnahmeposen hat das Potenzial, durch eine geeignete Trajektorienanpassung Messabweichungen zu reduzieren. In diesem Beitrag wird eine solche Trajektorienanpassung durch einen Hexapoden als Messobjektmanipulator und eine güteparameterbasierte Methodik zur Wahl einzelner Trajektorienpunkte erreicht. Die Ergebnisse zeigen, dass sich vor allem für eine geringe Projektionszahl signifikante Vorteile ergeben, was vor allem im Hinblick auf Inline-CT mit hohem Durchsatz von Relevanz ist.

Hans Lenk (1985): Die achte Kunst. Leistungssport – Breitensport. Osnabrück: Fromm. - Meier, Heiko (Sport und Gesellschaft)

Boundary Work in Generative AI Platforms: How Platform Providers Manage Complementors’ Changing Role - Mayer, Anne-Sophie; Kostis, Angelos; Strich, Franz; Holmström, Jonny (Academy of Management Proceedings)
Digital platforms increasingly integrate generative AI to dynamically create, optimize and adapt content with the aim to create novel opportunities for platform’s viability. However, the integration of GenAI into digital platforms fundamentally transforms complementors’ role as GenAI is able to autonomously generate content which was previously exclusively performed by complementors. To understand how platforms manage the changing role of complementors in response to AI generated content, we draw from an in-depth qualitative study of a digital learning platform. This empirical case allows us to explore which tensions arise between platform complementors and GenAI’s agency, and how the platform provider engages in different boundary work to manage the changing role of complementors to ensure the platform’s viability. Our study aims to contribute to the literature on GenAI and digital platforms.

The Emergence of Generative AI Platforms: The Changing Role of Complementors in Educational Practices - Mayer, Anne-Sophie; Strich, Franz; Kostis, Angelos; Holmström, Jonny (ECIS 2024 Proceedings)
Generative Artificial Intelligence (GenAI) systems empower platforms to dynamically create, optimize and adapt content promising to create novel benefits for platform’s viability. However, we know little about how the integration of GenAI into digital platforms redefines complementors’ role as a result of GenAI autonomously generating content which was previously exclusively performed by complementors. To understand how platforms can manage the changing role of complementors in response to AI generated content, we draw from an in-depth qualitative study of a digital learning platform. By using a boundary work lens, our empirical case allows us to explore which tension arises between platform complementors and GenAI, and how the platform provider engages in different practices to manage the changing role of complementors to ensure the platform’s viability. Our study aims to contribute to the literature on GenAI and digital platforms.

Charakterisierung des Verformungszustandes gleichartiger Stahl-Stahl-Clinchverbindungen durch Anwendung quantitativer Bildanalyse - Hollmer, Katharina; Kuczyk, Martin; Friedlein, Johannes; Mergheim, Julia; Steinmann, Paul; Zimmermann, Martina

Task-specific scan trajectory modification for dimensional X-ray computed Tomography with high throughput - Butzhammer, Lorenz; Hausotte, Tino (tm - Technisches Messen)

Innovation of the Platform Economy: Key Stakeholders and Starting Points for Sustainable Careers - Hofer, Annabelle; Rivkin, Wladislaw; Strich, Franz; Ihl, Andreas; Mayer, Anne-Sophie; Lei, Xue; Zhou, Lian; Huang, Xinran; Schweitzer, Vera M.; Genz, Sabrina; Gerten, Elisa; Trutwin, Lucas; et al. (Academy of Management Proceedings)
The platform economy introduces novel challenges and opportunities at the intersection of organizational structure, stakeholder relationships, and societal impact (Ashford et al., 2018; Caza et al., 2022; Cropanzano et al., 2023; Fieseler et al., 2019; Kuhn & Maleki, 2017). Following the call for rigorous methodological research on platform workers (Cropanzano et al., 2023), this symposium sheds light on the career development of platform workers by taking central stakeholders (e.g., workers, requesters, platform) into account. The five contributions cover diverse methodological approaches (e.g., longitudinal qualitative interviews, longitudinal quantitative surveys, diary studies), investigating online and offline platform workers from different online labor platforms (OLPs) in Asia, Europe, and the US. We bring together researchers from different fields (e.g., economics, management, psychology). They investigate how platform workers experience working on OLPs and how such experiences shape their careers. The symposium’s contributions collectively deepen our understanding of the platform economy by addressing platform design (cf. presentation [P] #P1, #P2), psychological aspects, such as well-being, linked to the interaction of workers with the requesters (cf. #P3), the decision-making of workers within the platform economy and its link to the gender pay gap (cf. #P4), and by proposing a novel framework of Transactional Careers to better understand the complex career development of platform workers (cf. #P5). This symposium will provide a platform for exchange among scholars from different fields interested in the platform economy to contributes substantial scientific implications for platform workers, policymakers, and OLPs for their important endeavor to develop a sustainable digitalized labor market, considering the role of different stakeholders.

Navigating Generative Artificial Intelligence Promises and Perils for Knowledge and Creative Work - Benbya, Hind; Strich, Franz; Tamm, Toomas (Journal of the Association for Information Systems)
Generative artificial intelligence (GenAI) is rapidly becoming a viable tool to enhance productivity and act as a catalyst for innovation across various sectors. Its ability to perform tasks that have traditionally required human judgment and creativity is transforming knowledge and creative work. Yet it also raises concerns and implications that could reshape the very landscape of knowledge and creative work. In this editorial, we undertake an in-depth examination of both the opportunities and challenges presented by GenAI for future IS research.

Who am I in the age of AI? Exploring dimensions that shape occupational identity in the context of AI for decision-making - Mayer, Anne-Sophie; Strich, Franz (Research Handbook on Artificial Intelligence and Decision Making in Organizations)
Organizations leverage artificial intelligence (AI) systems to augment or automate employee decision-making practices. These changes often transform employees’ occupation significantly and, thus, the way employees perceive themselves as professionals. By making use of qualitative insights from three case organizations that introduced AI systems for decision making, we explore how AI systems affect employees’ occupational identity. Our findings uncover three important dimensions that shape the way AI systems affect occupational identity. Based on our insights, we derive implications for the successful introduction of AI systems and highlight potential pitfalls that may arise from different organizational strategies used to introduce AI systems.

Thriving for Gig Workers’ Career Commitment: The Role of Platform Design Attributes - Strich, Franz; Andreas, Ihl; Anne Sophie, Mayer (ICIS 2024 Proceedings)
In gig work, individuals engage in project-based work outside traditional organizational structures. While some workers value the autonomy and flexibility of gig work, they also face unique challenges, including job insecurity and a lack of available career paths. Platforms are very limited in actively providing resources to their workers. However, platforms can shape their workers’ work environment by actively prioritizing different design attributes. Our study is among the first to uncover how these attributes contribute to workers’ intention to pursue a lasting career in gig work. Based on a PLS modelling approach with data from a two-wave quantitative survey involving 652 gig workers, we find that platforms’ utilitarian, hedonic, and relational design positively affect gig workers’ career commitment. Furthermore, we find evidence for the mediating role of gig workers’ thriving. Our research contributes to a better understanding of how platform design attributes can contribute to careers on gig work platforms.

Responsible Use of Artificial Intelligence: Decision-Making Through a Stakeholder Lens - Van-Hau, Trieu; Strich, Franz; Hind, Benbya
The rapid advancement of AI and automation is reshaping virtually every facet of contemporary business and society. Simultaneously, these emerging technologies also give rise to complex challenges for individuals and organizations to navigate. These challenges range from ensuring data privacy, and mitigating bias and discrimination, to maintaining transparency, trust, fairness and autonomy. Moreover, these challenges are differently perceived depending on the stakeholders involved. Our paper proposes a comprehensive framework that provides practical guidance based on 12 groups of questions for stakeholders to consider. We integrated and synthesized knowledge from three areas: responsible AI, stakeholder theory, and decision-making models. Our study seeks to enrich discourses on the responsible use of AI by providing a structured approach incorporating theoretical concepts with real-world applications.

Understanding the Wettability of C1N1 (Sub)Nanopores: Implications for Porous Carbonaceous Electrodes - Lamata‐Bermejo, Irene; Keil, Waldemar; Nolkemper, Karlo; Heske, Julian; Kossmann, Janina; Elgabarty, Hossam; Wortmann, Martin; Chorążewski, Mirosław; Schmidt, Claudia; Kühne, Thomas D.; López‐Salas, Nieves; Odziomek, Mateusz (Angewandte Chemie International Edition)
Abstract Understanding how water interacts with nanopores of carbonaceous electrodes is crucial for energy storage and conversion applications. A high surface area of carbonaceous materials does not necessarily need to translate to a high electrolyte‐solid interface area. Herein, we study the interaction of water with nanoporous C 1 N 1 materials to explain their very low specific capacitance in aqueous electrolytes despite their high surface area. Water was used to probe chemical environments, provided by pores of different sizes, in 1 H MAS NMR experiments. We observe that regardless of their high hydrophilicity, only a negligible portion of water can enter the nanopores of C 1 N 1 , in contrast to a reference pure carbon material with a similar pore structure. The common paradigm that water easily enters hydrophilic pores does not apply to C 1 N 1 nanopores below a few nanometers. Calorimetric and sorption experiments demonstrated strong water adsorption on the C 1 N 1 surface, which restricts water mobility across the interface and impedes its penetration into the nanopores.

Additive manufacturing of polymeric pressure die for rotary draw bending process - Kaleem, Muhammad Ali; Steinheimer, Rainer; Frohn-Sörensen, Peter; Gabsa, Steffen; Engel, Bernd (The International Journal of Advanced Manufacturing Technology)
Abstract 3D printing or additive manufacturing (AM) possesses enormous potential to benefit the manufacturing industry. Presently, rotary draw bending (RDB) is one of the most commonly used cold-forming industrial process for bending metal tubes. Pressure die is a fundamental forming tool in RDB processes, and it is conventionally made by various grades of comparatively expensive alloy steels. This research presents a novel design of a pressure die which can be 3D printed by using inexpensive polymeric filaments. In this research paper, the 3D-printed pressure die is named as “FFF-pressure die.” The material used to fabricate the FFF-pressure die is a thermoplastic polymer known as “ecoPLA.” The mechanical properties of ecoPLA are studied in relation to the process conditions of a RDB process. Firstly, an initial feasibility of using the FFF-pressure die in a RDB process is obtained by conducting a quick static stress analysis with actual process conditions. After initial feasibility, a complete RDB process is developed and simulated with actual process conditions and material properties. The FFF-pressure die is then practically fabricated by FFF 3D printer and experimentally tested on an industrial RDB machine. The results of practical experiments are compared with the simulation results. In order to make a comparison of the FFF-pressure die with the conventional metal pressure die, the simulation and practical process is also conducted with the conventional metal pressure die. A performance and cost comparison is made between the polymeric FFF-pressure die and the conventional metal pressure die. Von Mises stresses, contact forces, failure risk, and elastic deformations are analyzed. The advantages and limitations of using the FFF-pressure die in a RDB process are discussed in the end. This research intends to widen the avenue of using cost-effective and lightweight forming tools in metal forming industries.

Musik als Reformation - Reformation als Musik - Schroeter-Wittke, Harald (Menschlichkeit und Empathie. Brücken zwischen Kulturen und Konfessionen. Festschrift für Stefan Tobler zum 65. Geburtstag)

Who Let the Voices Out? Multivoicedness in Students’ Descriptions of Their Disciplines - Schmöckel, Sabrina